2016
DOI: 10.1002/pmic.201600121
|View full text |Cite
|
Sign up to set email alerts
|

Identification of common and differential mechanisms of glomerulus and tubule senescence in 24-month-old rats by quantitative LC-MS/MS

Abstract: Kidney aging together with related renal disease had become a major clinical problem. Understanding the mechanisms of aging was important for suspending senescence and decreasing the incidence of aging-related diseases. In the present work, 24-month-old F344 rats were used as aging rats and 3-month-old rats were used as young controls. Senescence-associated-β-galactosidase staining results showed that the degree of senescence in renal tubules was more severe than that in glomeruli. We performed quantitative LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Building on the pioneering studies that identified common senescence markers such as p21 and/or p16 and SA-βGal, several prior system biology-based efforts to discover signatures of senescence have applied transcriptomics or proteomics to examine replicative senescence [41, 42] and accelerated senescence [43] in cancer cells and in aging organs of human or animals [8, 9]. While these studies have revealed the common pattern of activation of inflammatory pathways linked to the SASP [10, 11, 44, 45], the gene expression patterns that underlie other characteristic features of senescence have remained largely obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on the pioneering studies that identified common senescence markers such as p21 and/or p16 and SA-βGal, several prior system biology-based efforts to discover signatures of senescence have applied transcriptomics or proteomics to examine replicative senescence [41, 42] and accelerated senescence [43] in cancer cells and in aging organs of human or animals [8, 9]. While these studies have revealed the common pattern of activation of inflammatory pathways linked to the SASP [10, 11, 44, 45], the gene expression patterns that underlie other characteristic features of senescence have remained largely obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed senescence is a recently described feature of early development [7]. Common features of these diverse forms of senescence include enlarged cell size, unrepaired genomic damage, proliferative arrest linked to expression of the p21 CIP/WAF1 and/or p16 Ink4A stoichiometric cyclin-dependent kinase inhibitors, and activation of senescence-associated β-galactosidase activity (SA-β-Gal) [812].…”
Section: Introductionmentioning
confidence: 99%
“…The labeled fractions were analyzed using the Lumos mass spectrometer as described previously . For details, see supplemental online Appendix 1.…”
Section: Methodsmentioning
confidence: 99%
“…The data analysis was similar to that described in a previous study [8]. Proteome Discoverer from UniProt (version PD1.4, Thermo-Fisher Scientific) was used to analyze the raw data with the human database.…”
Section: Discussionmentioning
confidence: 99%
“…The tumors and adjacent normal tissues were ground with liquid nitrogen in a mortar and dissolved in fresh lysis buffer (8 M urea in PBS, pH 8-8.5, 1 mM PMSF, and 1 mM protease inhibitor cocktail). The digestion process was similar to that used in a previous study [8]. Briefly, protein content was determined using the BCA Protein Assay Kit (Thermo-Fisher Scientific, Rockford, IL, USA), in accordance with the manufacturer's instructions.…”
Section: Protein Digestion and Liquid Chromatography-tandem Mass Specmentioning
confidence: 99%